Incidence and Organism Specific Mortality Associated with Healthcare Associated Pneumonia Over a Six Year Period. (4th October 2017) - Maki, Gina; Xin, Yuan; Zeeshan, Nikhath; Harris, Anthony; Lawrence, Steven J; Masica, Andrew; Lamerato, Lois; Zervos, Marcus
Abstract: Background: Healthcare-associated pneumonia (HCAP) is a common and potentially life threatening illness. Pneumonia is one of the most common causes of healthcare associated infections. The purpose of our study was to investigate in a large multicenter cohort over a several year period, the association of specific organisms with patient mortality in HCAP patients. Methods: This is a retrospective multicenter analysis of patients over 18 years of age hospitalized with HCAP over a 6-year period from 2008 to 2013 from 4 large healthcare institutions. Patients were identified by electronic medical record review. HCAP was defined by inclusion of patients with a discharge diagnosis of pneumonia by ICD-9 code plus associated antibiotic use in the initial 24 hours. Patients were considered to have HCAP if initial antimicrobial use included one of the following: cefepime, doripenem, meropenem, imipenem, or piperacillin-tazobactam, in combination with vancomycin or linezolid. Results: There were 16084 patients. Staphylococcus aureus was the most common organism isolated in 368 patients and had 15.0% mortality at 30 days. Pseudomonas aeruginosa was isolated in 359 patients and had 24.2% mortality at 30 days. Acinetobacter baumannii was isolated in 200 patients, and accounted for 34.0% mortality. Escherichia coli was isolated in 89 patients with 24.7% mortality. Klebsiella pneumoniae was isolated in 99 patients with 27.3% mortality. Commensal bacteria were isolated or positive cultures with no speciation occurred in 5214 of patients with 22.8% mortality at 30 days. The remaining patients did not have organisms identified in the blood or sputum. Conclusion: Most patients with HCAP did not have an organism isolated. Mortality rate in these patients was generally similar to patients in whom an organism was identified except for S. aureus and A. baumannii . In patients from whom organisms were identified, S. aureus was most common and E. coli was the least common. Thirty-day mortality was highest in A. baumannii, and lowest with S. aureus . The lower mortality in patients with S. aureus is potentially related to early effective therapy. The high percentage of deaths due to A. baumannii is potentially related to both severe underlying disease and multidrug resistance limiting therapy options. Disclosures: M. Zervos, Merck: Investigator, Research grant; Genentech: Investigator, Research grant; Cempra: Investigator, Research grant; Pfizer: Investigator, Research grant